Can Genomics of Gut Microbiota in Stool Samples be Analysed by MERLIN? - Kamaruddin, Mudyawati (Journal of Intelligent Computing & Health Informatics, 2022)
Metagenomics is important for studying microorganisms that live in microbial communities, particularly those inhabiting the human body. For instance, the gut microbiota is a community of microorganisms that reside in the human gut and interact with humans through secondary metabolites. These metabolites produced by the gut microbiota are extremely important and serve as precursors for various human needs, such as short chain fatty acids (SCFA). While there have been reports of functional secondary metabolites produced by different gut microbiota, none have been utilized on the Merlin platform. In this article, we will examine how the Merlin platform can analyze the gut microbiota community. Metabolic Models Reconstruction using Genome-Scale Information (MERLIN) is a bioinformatics tool that can analyze the functional microbial community as well as the taxonomy of these bacteria.